Phosphodiesterase 1 regulation is a key mechanism in vascular aging - Niño, Paula K Bautista; Durik, Matej; Danser, A H Jan; de Vries, René; Musterd-Bhaggoe, Usha M; Meima, Marcel E; Kavousi, Maryam; Ghanbari, Mohsen; Hoeijmakers, Jan H; O'Donnell, Christopher J; Franceschini, Nora; Janssen, Ger M J; et al. (Clinical science (1979), 2015)
Reduced nitric oxide (NO)/cGMP signalling is observed in age-related vascular disease. We hypothesize that this disturbed signalling involves effects of genomic instability, a primary causal factor in aging, on vascular smooth muscle cells (VSMCs) and that the underlying mechanism plays a role in human age-related vascular disease. To test our hypothesis, we combined experiments in mice with genomic instability resulting from the defective nucleotide excision repair gene ERCC1 (Ercc1(d/-) mice), human VSMC cultures and population genome-wide association studies (GWAS). Aortic rings of Ercc1(d/-) mice showed 43% reduced responses to the soluble guanylate cyclase (sGC) stimulator sodium nitroprusside (SNP). Inhibition of phosphodiesterase (PDE) 1 and 5 normalized SNP-relaxing effects in Ercc1(d/-) to wild-type (WT) levels. PDE1C levels were increased in lung and aorta. cGMP hydrolysis by PDE in lungs was higher in Ercc1(d/-) mice. No differences in activity or levels of cGMP-dependent protein kinase 1 or sGC were observed in Ercc1(d/-) mice compared with WT. Senescent human VSMC showed elevated PDE1A and PDE1C and PDE5 mRNA levels (11.6-, 9- and 2.3-fold respectively), which associated with markers of cellular senescence. Conversely, PDE1 inhibition lowered expression of these markers. Human genetic studies revealed significant associations of PDE1A single nucleotide polymorphisms with diastolic blood pressure (DBP; β=0.28, P=2.47×10(-5)) and carotid intima-media thickness (cIMT; β=-0.0061, P=2.89×10(-5)). In summary, these results show that genomic instability and cellular senescence in VSMCs increase PDE1 expression. This might play a role in aging-related loss of vasodilator function, VSMC senescence, increased blood pressure and vascular hypertrophy.
Keywords: celogenomová asociační studie; Endonucleases; Hydrolysis; vazodilatace; Polymorphism, Single Nucleotide; hyperplazie; inhibitory fosfodiesterasy 5; DNA-Binding Proteins; techniky in vitro; regulace genové exprese u nádorů; Humans; Cyclic Nucleotide Phosphodiesterases, Type 5; DNA vazebné proteiny; Vasodilation; hydrolýza; stárnutí buněk; vazodilatancia; Hypertension; jednonukleotidový polymorfismus; Dose-Response Relationship, Drug; Myocytes, Smooth Muscle; stárnutí; Phenotype; svaly hladké cévní; lidé; Cyclic GMP; zvířata; Cells, Cultured; Aging; Hyperplasia; Phosphodiesterase 5 Inhibitors; myši inbrední C57BL; cyklické nukleotidfosfodiesterasy, typ 1; cyklické nukleotidfosfodiesterasy, typ 5; myši knockoutované; Carotid Intima-Media Thickness; Carotid Arteries; endonukleasy; Cyclic Nucleotide Phosphodiesterases, Type 1; krevní tlak; myocyty hladké svaloviny; Mice, Knockout; Second Messenger Systems; hypertenze; kultivované buňky; fenotyp; genetická predispozice k nemoci; Genetic Predisposition to Disease; Mice, Inbred C57BL; In Vitro Techniques; systémy druhého messengeru; guanosinmonofosfát cyklický; Genome-Wide Association Study; vztah mezi dávkou a účinkem léčiva; Cellular Senescence; Animals; Vasodilator Agents; nemoci arterie carotis; Gene Expression Regulation, Neoplastic; Muscle, Smooth, Vascular; Blood Pressure; Carotid Artery Diseases; intimomediální šíře tepenné stěny; arteriae carotides